Mother's Knowledge and Attitudes About Diarrhea Management in Children - Zusana A Sasarari; Yuriatson Yuriatson; Darmi Arda; Andi Suyatni Musrah; Ria Wahyuni (Jurnal Edukasi Ilmiah Kesehatan, 2023)
Diarrhoea is the leading cause of morbidity and mortality in children worldwide, including in Indonesia. The magnitude of the problem can be seen from the high rate of pain and death due to diarrhea. The study aims to determine mothers' knowledge and attitudes about treating diarrhea in children. Experimental quantitative research with a descriptive approach. The results showed that the level of knowledge was less than 25 people (62.5%), and the negative attitude category was 29 people (72.5%). It can be concluded that they suffer from diarrhea, while parents with good knowledge regarding managing diarrhea tend to have their children not suffer from diarrhea. Recommendations are expected to provide information for local health offices and puskesmas in overcoming diarrhea problems; this is valuable information to carry out programs to improve public health, especially diseases in children.